Physiochemical properties and electromagnetic wave absorption performance of Ni0.5Cu0.5Fe2O4 nanoparticles at X-band frequency - Wahaab, F.A. (Elsevier Ltd, 2020)
Due to the unremitting emission of electromagnetic (EM) wave pollution from electronic and electrical devices, the fabrication of materials with EM waves absorption capacity is an active research domain. Ferrite nanoparticles are one of the widely studied materials in the area of EM wave absorption. Hence in this work, Ni0.5Cu0.5Fe2O4 nanoparticles were synthesized using four different coprecipitating agents (NaOH, KOH, NH4OH, and Na2CO3). The structure, composition, morphology, magnetic and thermal properties of all the samples were characterized and compared using XRD, FT-IR, XPS, FESEM, VSM and TGA analysis, respectively. The effect of coprecipitating agents on the EM properties of all the samples for optimum EM wave absorption was investigated and presented within the X-band frequency range. The Ni0.5Cu0.5Fe2O4 nanoparticles prepared with NH4OH was identified as the optimal material due to its superior physiochemical and EM properties. An enhanced EM wave absorption with optimum RL of â42.1 dB was achieved with the optimal material at 11.7 GHz, with 3.5 mm thickness. The material has an absorption bandwidth of 1.51 GHz. Thus, the use of NH4OH amongst other coprecipitants for Ni0.5Cu0.5Fe2O4 synthesis is more favorable for EM wave absorption application. Â© 2020 Elsevier B.V.